2016
DOI: 10.15171/jarcm.2016.024
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and risk factors of attention deficit hyperactivity disorder among the elementary school students in Ardabil, Iran, in 2011-2012

Abstract: Introduction: Attention deficit hyperactivity disorder (ADHD) is the most prevalent neurodevelopmental disorder among children and adolescents. Given the importance of this disorder, the aim of this study was to investigate the prevalence of ADHD and the relevant factors among the elementary school students in Ardabil, Iran. Methods: Using the stratified random cluster sampling method, this cross-sectional descriptive study was conducted on 2826 schoolchildren aged 6-11 in Ardabil, in the year 2011-2012. The n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
2
2
2
Order By: Relevance
“…ADHD symptoms were more prevalent in boys than girls in this study which is compatible with the results of Amiri et al, 15 Abolhassanzadeh et al, 16 Bener et al, 17 and Mugnaini et al 18 This perhaps results from development of more obvious symptoms in boys than affected girls; for example the majority of boys with ADHD are impulsive and most of the girls with ADHD are inattentive.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…ADHD symptoms were more prevalent in boys than girls in this study which is compatible with the results of Amiri et al, 15 Abolhassanzadeh et al, 16 Bener et al, 17 and Mugnaini et al 18 This perhaps results from development of more obvious symptoms in boys than affected girls; for example the majority of boys with ADHD are impulsive and most of the girls with ADHD are inattentive.…”
Section: Discussionsupporting
confidence: 91%
“…These are in agreement with the studies conducted by Alishahi et al, 19 and Shahim et al, 20 while different from the study of Abolhassanzadeh et al 16 in which hyperactive/impulsive type was the most frequent one. This difference may be due to different sampling methods noticing that combined and predominantly inattentive types are more common in the clinical population than hyperactive/impulsive type.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is consistent with the result obtained by Alishahi et al (27), Shahim et al (28). Conversely, it is inconsistent with the result by Abolhassanzadeh et al (22), in which they found the impulsive/hyperactive subtype as the most frequent in ADHD. This finding is mostly related to environmental, social, and cultural factors.…”
Section: Discussioncontrasting
confidence: 82%
“…Low family socio economic status was found to be significantly associated with ADHD in the study of Lola et al 20 A review of literature done by Kapil Sayaletal also found that children from low socioeconomy had 1.5 to 4 times more likely to have ADHD. 34 A study done in the UK on the Socioeconomic Associations with ADHD found that the risk of developing ADHD will be doubled if their parents were in financial problem during infantile age. 35 This is also found in the study done in Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the longitudinal study of Wüstner et al, where more incidence of ADHD was noted in children from low socioeconomic status. 34 This is due to the fact that stressors cause various neuroendocrine responses which in turn predispose to several mental illnesses as explained by Kaplan and Sadocks. 2 We found no association between maternal substance use and ADHD.…”
Section: Discussionmentioning
confidence: 99%